Bio-inspired algorithms for engineering - Alanis, Alma Y.; Arana-Daniel, Nancy; Lopez-Franco, Carlos (Butterworth-Heinemann, an imprint of Elsevier, 2018)
"Bio-inspired Algorithms for Engineering builds a bridge between the proposed bio-inspired algorithms developed in the past few decades and their applications in real-life problems, not only in an academic context, but also in the real world. The book proposes novel algorithms to solve real-life, complex problems, combining well-known bio-inspired algorithms with new concepts, including both rigorous analyses and unique applications. It covers both theoretical and practical methodologies, allowing readers to learn more about the implementation of bio-inspired algorithms. This book is a useful resource for both academic and industrial engineers working on artificial intelligence, robotics, machine learning, vision, classification, pattern recognition, identification and control. Presents real-time implementation and simulation results for all the proposed schemes. Offers a comparative analysis and rigorous analysis of the convergence of proposed algorithms. Provides a guide for implementing each application at the end of each chapterIncludes illustrations, tables and figures that facilitate the reader's comprehension of the proposed schemes and applications"--